2020
DOI: 10.1177/1362168820934624
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness in the foreign language classroom: Influence on academic achievement and awareness

Abstract: Incorporating mindfulness into education has been linked to improving academic, social and emotional learning. This article describes an investigation of the implementation of meditative practices in a foreign language setting (German). Two classes underwent distinct varieties of meditation: The count-to-ten method and the guided meditation approach, whereas a third class served as a comparison group by not partaking in meditative activities. Meditative practices were implemented for a period of one y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 57 publications
0
18
0
Order By: Relevance
“…The trainability of SI is in line with the idea that it has an adaptive nature, and contributes to the idea of neuroplasticity (Ferreira, 2014). This would not be a far‐fetched idea as previous research has demonstrated the adaptive nature of such SI indices as humility (e.g., Emmons, 2000) and mindfulness (e.g., Moore & Malinowski, 2009; Zeilhofer, 2020), which to a large extent contribute to SI.…”
Section: Discussionmentioning
confidence: 99%
“…The trainability of SI is in line with the idea that it has an adaptive nature, and contributes to the idea of neuroplasticity (Ferreira, 2014). This would not be a far‐fetched idea as previous research has demonstrated the adaptive nature of such SI indices as humility (e.g., Emmons, 2000) and mindfulness (e.g., Moore & Malinowski, 2009; Zeilhofer, 2020), which to a large extent contribute to SI.…”
Section: Discussionmentioning
confidence: 99%
“…Mortimore (2017) emphasizes the contribution of different mindfulness-oriented meditation practices to create a more effective classroom atmosphere by positively affecting FL learning and attention orientation. Zeilhofer (2020) asserts that due to its repetitive nature, meditation practices can support better vocabulary learning in the FL class along with their positive effects on academic achievement in general and focused attention that supports FL learning. It is further pinpointed that guided meditation exercises in the FL classroom can result in better grades and increased mindfulness towards FL learning (Zeilhofer, 2020).…”
Section: Mindfulness and Foreign Language Teachingmentioning
confidence: 99%
“…Zeilhofer (2020) asserts that due to its repetitive nature, meditation practices can support better vocabulary learning in the FL class along with their positive effects on academic achievement in general and focused attention that supports FL learning. It is further pinpointed that guided meditation exercises in the FL classroom can result in better grades and increased mindfulness towards FL learning (Zeilhofer, 2020).…”
Section: Mindfulness and Foreign Language Teachingmentioning
confidence: 99%
See 2 more Smart Citations